PENERAPAN MODEL PEMBELAJARAN MULTILITERASI INFORMASI BERBANTUAN MEDIA KARTU TEKS DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA TEKS EKSPOSISI SISWA KELAS IV - Nurul Aulia, Shafa; Sri Wulan, Neneng; Mulyani, Srie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the low ability to read comprehension of exposition text in grade IV students. Based on the results of the data obtained at the pre-cycle stage the ability to read comprehension of exposition texts of SDN 2 Batutumpang students is still low. The researchers took action by applying the Multiliteracy Information model assisted by Text Card media during learning activities to improve the ability to read comprehension of exposition texts of grade IV students. This research used the Classroom Action Research (PTK) method with Kemmis and McTaggart design for 2 cycles. This research was conducted in class IV of SDN 2 Batutumpang with research subjects 26 male students and 14 female students.  After applying the Information Multiliteracy model assisted by Text Card media, there was an increase in students' ability to read comprehension of exposition text. The results of teacher and student activities in cycle 1 showed an increase of 90% and rose to 100% in cycle 2. Cycle 1 obtained an average score of 67 with 20 students and a percentage of classical completeness of 55%. Cycle 2 obtained an average score of 82 with 35 complete students and a percentage of classical completeness of 87%. Thus, it can be concluded that applying the Multiliteracy Information learning model assisted by Text Card media can improve reading comprehension.   Keywords: multiliteracy information, reading comprehension, exposition text, text card media